Occurrence of sulphate efflorescences in São Domingos mine - Gomes, P. (2017)
The intense exploration of sulphide ore deposit in São Domingos mine, produced considerable amount of sulphide material that when are exposed to weathering generates acid mine drainage (AMD). The main goal of this paper is to study a specific occurrence regarding composition and morphology of the salts that arise at the end of the dry season. Soluble salts appear at the banks of the drainage channels and over the waste materials, exhibiting different colours and aspects. The obtained results showed by X-Ray diffraction and scanning electronic microscopy, that the mineralogy of salt efflorescences is dominated by sulphates, displaying different occurrence modes. Melanterite and copiapite are the main iron sulphates while minerals from the series of pickeringite-halotrichite dominate the aluminium sulphates. In addition, dehydration and dissolution laboratory experiments were carried out in order to simulate the transformations suffered by soluble salts and evaluate the environmental effect in aquatic system.